Activity of manganese superoxide dismutase (MnSOD) as a predictor of radiation therapy outcome in patients with stage IIIB squamous cell carcinoma cervical cancer (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Radiation is a standard therapy for cervical cancer. Unfortunately, not all patients undergoing radiation achieve a complete response. Previous studies have shown that manganese superoxide dismutase (MnSOD) acts against free radicals generated by radiation in cancer cells thus predicting worse outcome in radiation therapy. This study was aimed to assess and evaluate whether MnSOD activity can be used as a predictor of radiation therapy responses in patients with stage IIIB squamous cell carcinoma (SCC). METHODS A comparative cross-sectional study was conducted in the Gynecology Oncology Division, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital, Jakarta. The database from previous research was analyzed to identify positive and negative response samples. Measurement of MnSOD activity was done using spectrophotometry based on the McCord and Fridovich method using RanSOD® kit. The comparative data were obtained and then analyzed. RESULTS Among 76 samples, 49 (61.8%) patients had positive responses and 27 (38.2%) had negative responses. It is shown in this study that higher MnSOD activity is related to worse radiotherapy outcome in stage IIIB cancer patients. The relative risk value of having a worse outcome with high MnSOD activity is 1.849 (1.075-3.178, 95% CI). CONCLUSIONS Stage IIIB squamous cell carcinoma patients with high MnSOD activity are at higher risk of having a negative radiation therapy response compared with patients without high MnSOD activity.